Correlation Between Mastery of Music Theory, Solfegio, and Profiency in Playing Primary Music Insrument at The Intermediate Level in Music Program, Universitas Negeri Surabaya (Universitas Negeri Semarang, 2023)
This research aimed to determine whether there is a significant correlation between mastery of music theory, solfeggio, and skills in playing primary music instruments at the intermediate level in the Music Arts Study Program at the State University of Surabaya. The research employed quantitative method with correlational research design. Pearson product-moment correlation analysis was used as the correlational research technique. The prerequisite test indicated that the data followed a normal distribution and that the independent variable and the dependent variable exhibited a linear or symmetrical relationship. The research results revealed a very strong relationship, as evidenced by a Pearson correlation coefficient of 0.893** and 0.891**. The two-star sign (**) in the results indicates a significant correlation with a significance value of 0.000 and a two-tailed possibility. The positive correlation coefficient indicates a unidirectional relationship between the variables. Thus, the research results show a significant relationship between mastery of music theory, solfeggio, and intermediate level playing skills on primary music instruments in the Music Arts Study Program at State University of Surabaya. This conclusion is supported by the significance value of 0.000 for both the mastery of music theory variable and the knowledge of solfeggio variable in relation to the intermediate level playing skills on primary music instruments. The calculated significance value (sig o) was found to be less than 0.05 (0.01), confirming the statistical significance of the results.